Arquitetura de subsunção baseada em objetivo de controle principal - Santos, Phillipe Cardoso (2017)
A very important aspect in robotics is the decision making and execution the system uses to achieve its goals. In literature, many different approaches can be found about how the robot must behave in different situations in order to have a more robust system. Subsumption architecture is one of the most used and referenced in the area. In this architecture, the global task is divided into subtasks which are performed by behaviors organized in hierarchical layers. However, little research has been done regarding the stability analysis of this architecture. Behavioral changes imply in controller switching, which can lead the system to instability even in cases where all controllers are stable. In this work, a subsumption architecture with guaranteed stability is presented based on the theory of switched systems with main control objective. In addition, a formalism capable of allowing behaviors modeling in a simple and fast way is proposed based on the theory of discrete events systems. Tests in real environments were performed with the Pioneer P3-DX robot and obtained results demonstrate the proposed approach effectiveness.